DeterminingSelf-Confidence Resources in Elite Bodybuilders and Their RelationshipwithBody Image - Hassan Kiaei; Jafar Nouri; Elaheh Shojaei (University of Tehran, 2016)
The present study aimed at determining resources of sport self-confidence in elite bodybuilders and their relationship with body image. The subjects of study included 35 bodybuilders participating in qualifying tournaments of bodybuilding national team. A questionnaire for resources of sport self-confidence and a questionnaire of physical self-description were used to collect data. Kolmogorov-Smirnov test, one-sample ttest, Pearson correlation coefficient and one-variable regression with significance level of 0.05 were used to analyze data. The findings showed that ability demonstration (Mean=6.451 ± 0.787) was the most important resource of sport self-confidence in elite bodybuilders. Moreover, the results showed that bodybuilders had a positive body image (t(16.82)=31.94, P<0.001). Regarding the correlation between resources of sport self-confidence and body image, the results showed a positive and significant relationship between all resources of sport self-confidence (except for the vicarious experiences and coaches' leadership style) and body image and the highest level of correlation belonged to ability demonstration with body image (P<0.001, r=0.5920). Furthermore, the results showed that the body image of these bodybuilderswas a predictor of their sport self-confidence (β=0.520, t=3.497, P<0.001). The results of this study support Vealey's sport self-confidence model.